THE RELATIONSHIP BETWEEN NATURAL RESOURCES AND HUMAN RESOURCES IN ECONOMIC LIFE IN PASURUAN CITY - Alya Nur Putri Natasya; Fany Fadilah; Hilmiyatusoliha; Nurus Sobakh (Yayasan Amanah Nur Aman, 2026)
This study explores the state of natural resources and human resources in Pasuruan City and their relationship in supporting the pace of regional economic growth. The city of Pasuruan has significant potential for the application of natural resources, especially in the fisheries, agriculture, industry, and tourism sectors. Its favorable geographical position also contributes to the development of the economic activities of the local community. However, the use of natural resources has not been fully maximized because there are various challenges, especially related to the low quality of human resources in some regions. Low education, skills, experience, and lack of training and application of technology are obstacles in the efficient and sustainable management of natural resources. In addition, environmental issues such as pollution and overexploitation of resources are also issues that need attention. This study applies a qualitative descriptive method by analyzing the state of natural resources and human resources in Pasuruan City based on various data sources and relevant discussions. The findings of the study show that the relationship between natural resources and human resources is very close, because the success of natural resource management is greatly influenced by the quality of human resources as the main manager. Therefore, it is necessary to make various efforts to improve the quality of human resources through education, training, technology utilization, strengthening business institutions, and sustainable natural resource management. With the improvement of the quality of human resources and good natural resource management, it is hoped that regional economic growth can increase and the welfare of the people of Pasuruan City can be achieved in a sustainable manner.